Influence of Internal Service Quality and Career Development on Employee Performance through Organizational Citizenship Behavior - Angkasa Maharani, Indah; Nurhayati, Mafizatun (Dinasti Publisher, 2024)
This study aims to analyze the factors that influence the employee performance at PT. Leschaco Logistic Indonesia. The population of this research is employees of PT. Leschaco Logistic Indonesia with a total sample of 148 permanent employees. The data analysist method used Structural Equation Model-Partial Least Square (SEM-PLS). The research results show that internal service quality has an influence on employee perfomance. Furthermore, organizational citizenship behavior act as mediating role between internal service quality and career development on employee performance. However, on the other side, career development has no influence on employee performance. Employee performance is influenced by caring between colleagues and a positive work environment with minimal conflict can increase employee performance. However, self-development which held by the company is not able to increase employee performance